Microstructure and some properties of powder-pack borided Ti–5Mo–5V–8Cr–3Al alloy with special attention to the microstructure at the interface TiB/substrate. Issue 17 (1st September 2022) - Wu, Ying; Zhou, Xiaolong; Wang, Xinyu; Lu, Yaoping; Peng, Mingjun; Duan, Yonghua
Abstract: The borided layer was prepared on the surface of the Ti–5Mo–5V–8Cr–3Al alloy by powder-pack boriding at 1000°C-10h. SEM, EPMA and TEM were used to investigate the effects of alloying elements (Al, V, Mo and Cr) on the growth of TiB whiskers in the borided Ti–5Mo–5V–8Cr–3Al alloy. Wear properties of borided Ti–5Mo–5V–8Cr–3Al alloy were investigated using dry reciprocating friction tests. SEM results show that the thickness of boride layer in Ti–5Mo–5V–8Cr–3Al alloy is thinner than that in the Cp-Ti. This is attributed to the enrichment of alloying elements especially V in TiB/substrate by TEM, which hinders the diffusion of B atoms, thus resulting in the short and thick TiB whiskers in Ti–5Mo–5V–8Cr–3Al alloy. Borided Ti–5Mo–5V–8Cr–3Al alloy has the better wear resistance than as-received alloy.